Shifting Paradigms: Rethinking Education During and Post-COVID-19 Pandemic - Hlamulo Wiseman Mbhiza (Research in Social Sciences and Technology, 2021)
It is uncontested that education systems globally are under constant pressure to respond to the changing needs of societies. The outbreak of Covid-19 has reminded us that the complexity of education needs responsive practices to facilitate effective teaching and learning across all levels of schooling globally. All over the world, the normative ways of teaching and learning evolved drastically in the first quarter of the 2020 academic year when teachers and students found online offerings to be the dominant option available as a consequence of the pandemic conditions. In South Africa specifically, students and teachers were thrust into virtual teaching and learning situations with the majority of them having no preparation for this shift. This conceptual paper considers education in the current and post-Covid-19 era as the greatest paradigm shift in the history of education. I examine measures taken by higher education institutions to support the provision of education to ensure learning continuation. In this paper, I provide some suggestions for carrying out educational activities during the continuing Covid-19 situation. Educational leaders need to rethink content creation and content sharing and establish working communities to meet the demands of the new paradigm in education.